Pengaruh Daya Tarik, Kredibilitas, dan Popularitas Brand Ambassador terhadap Keputusan Pembelian Mie Sedaap melalui Brand Image sebagai Variabel Mediasi - Petronella Gabrina Simatupang; Imroatul Khasanah (Faculty of Economics and Business Diponegoro University, 2025)
In recent years, the rising presence of Korean celebrities in marketing campaigns across Indonesia has reflected a shift in brand communication strategies—one that emphasises emotional resonance between public figures and consumers. Mie Sedaap, a wellknown instant noodle brand, adopted this approach by appointing South Korean actor Ahn Hyo Seop as its brand ambassador, aiming to capture the attention of younger audiences and shape a favourable perception of the brand. This study explores how consumers perceive the brand ambassador’s attractiveness, credibility, and popularity, and how these perceptions influence their purchase decisions, with brand image positioned as a mediating variable. The research applies a quantitative approach, using an online questionnaire distributed to 142 respondents who are Mie Sedaap consumers in Semarang. The collected data were analysed using Structural Equation Modelling (SEM) with AMOS 24. The findings indicate that all three attributes of the brand ambassador, attractiveness, credibility, and popularity, positively and significantly influence brand image. In turn, brand image shows a significant positive effect on consumer purchase decisions. Overall, the results highlight the strategic importance of choosing a brand ambassador who is not only visually appealing but also trustworthy and socially influential. When these elements are present, they help shape a stronger brand image that ultimately encourages consumer purchases. These insights provide valuable guidance for marketers seeking to design campaigns that resonate with the emotional and aspirational needs of today’s market.